Analisis Kontribusi Hukum Terhadap Pembangunan Ekonomi Nasional Indonesia - Ali Yapi; Robby Nurdiansyah; Deni Mulyawan; Neng Endah; Dion Mandala Putra; Damei Erman Herdinasta (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
Indonesia's national legal development is a crucial effort to create a legal system aligned with the values of Pancasila and the 1945 Constitution. The Indonesian government needs to orient itself towards developed countries in several aspects and consider the importance of communication technology and investment in national development strategies. Development aims to transform society to a better condition by eliminating outdated values and promoting new ones to adapt to changing times. International trade, as a pillar of the global economy, plays a significant role in driving economic growth, job creation, and improving public welfare. However, challenges in creating a fair-trade system require the application of justice principles in international trade law. Investment also plays a vital role in economic growth, supported by regulations such as Law No. 25 of 2007 on Investment and the Omnibus Law policy to create a conducive investment climate. This study discusses the legal certainty of foreign investment in Indonesia and the evaluation of investment regulation reform through the Omnibus Law, as well as how labor regulations can support labor protection and a conducive investment climate